Performance analysis and economic evaluation of thermosyphon paddy bulk storage - Dussadee N. (2014)
Performance and economic analyses of a prototype paddy bulk storage with R22 thermosyphon for self-heat rejecting have been studied. The unit has a steel cylindrical bin with diameter of 1250 mm and length of 1500 mm that contains 1000 kg of paddy. The evaporation section of the thermosyphon embedded in the paddy bulk is a set of copper tubes with the total heat transfer area of 8.5 m2. The condenser section with the total area of 12.2 m 2 is exposed to the ambient air. The analyses have been compared with the unit having a conventional aeration. The experiment shows that there is a high potential for using thermosyphon to control the paddy bed temperature. It could be found that for the paddy with moisture content of 26.9% and 13.5% wet basis, the thermosyphon can maintain the paddy bed temperature at 37-38 °C and 28-29 °C, respectively compared with 62 °C and 31-32 °C for the unit without any control. Moreover very small temperature difference in the bed is also observed in the unit with thermosyphon. The paddy quality in term of head rice yield (38.06%), percentage of brown (72.7%) and white rice (60.14%) for the unit with thermosyphon is very close to those (40.16%, 72.37%, 60.43%) of the unit with aeration. The mathematical model developed could be used to predict the paddy bed temperature accurately and the evaporator area should not be less than 16 m2 for 1000 kg of paddy (Condenser area of 12.2 m2) at Chiang Mai, Thailand. The economic analysis indicates that the payback period of the storage with 16 m2 evaporator area is shorter and higher IRR obtained with the percent of annual fan operation. The payback is about 8 years when 20% of annual fan operation is taken. © 2003 Elsevier Ltd. All rights reserved.